Pengaruh Pengaruh Latihan Lunges dan Squat Jump terhadap Kekuatan Otot Tungkai pada Atlet DATC Rembang - Sabrina Violeta Anggraini; Sahri Sahri (Ilmu Olahraga, 2026)
Taekwondo relies heavily on leg muscle strength, as it plays a crucial role in producing effective and explosive kicks. An appropriate training program is necessary to optimize muscle power production. This study aims to analyze whether there is an influence on leg muscle strength and compare the effectiveness of the two methods on taekwondo athletes at DATC Rembang from lunges and squat jumps. Experimental research was implemented using a pretest–posttest control group design. Twenty taekwondo athletes aged 13 to 18 served as subjects, divided into two treatment groups: the lunges group and the squat jump group. The training program was conducted for six weeks, three times per week. A digital leg dynamometer was used to measure leg muscle strength, and the Shapiro–Wilk test, Levene's test, paired sample t-test, and independent sample t-test were implemented to analyze the data with a significance level of 0.05. The research findings showed that leg muscle strength is significantly effected by training methods (p < 0.05), and there was a significant difference between the two methods, with squat jumps being more effective than lunges. It can be concluded that leg muscle strength in adolescent taekwondo athletes can be optimally improved by plyometric-based training.